PERCEPTION OF PARENTS AND RELATIVES ABOUTHE THE GENERAL EXPOSITION OF THE NEWBORN TO HARMFUL AGENTS: PERCEPTION OF PARENTS AND RELATIVES ABOUTHE THE GENERAL EXPOSITION OF THE NEWBORN TO HARMFUL AGENTS - Silva, Damiana Gomes da; Silva , Macerlane de Lira; Bezerra , Yuri Charllub Pereira; Quental , Ocilma Barros de (Brazilian Journal of Production Engineering, 2020)
Introduction: The neonatal phase is a period of adaptation, since the extrauterine environment makes the baby exposed to agents which can cause harm, such as infections, which are the responsible for the crescent numbers of morbidity. The family is maintainer of the baby’s health; therefore, they need correct orientation. Purpose: To show the perception of the family on the exposition of the newborn to harmful agents. Methods: This is an integrative review of the literature, made with the databases: Virtual Health Library (VHL), Latin American and Caribbean Literature on Health and Science (LILACS) and Scientific Electronic Library Online (SCIELO), from 2014-2019, full text and available in Portuguese. The descriptors used were: newborn; family relationship; risk factors; mortality; sepsis; nosocomial infection; with the use of the Boolean operator “and”. Results: Were identified 4.846 documents and after selection with filters there were only 318 left. After analysis, some were also excluded for (title, text, duplicity, etc.), leaving only 09 articles left. Prevalence of researches that used descriptive/ quantitative methods. Final Considerations: The parents are the maintainers of the newborn, which they don’t always know how to take care, health education is essential on prevention, especially in areas of poverty.
Keywords: Newborn; relatives; risk factors; mortality; sepsis; nosocomial infection; care; neonatal health; prevention.